2013
DOI: 10.1371/journal.pone.0060204
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Optimum Sequencing Depth Especially for De Novo Genome Assembly of Small Genomes Using Next Generation Sequencing Data

Abstract: Next Generation Sequencing (NGS) is a disruptive technology that has found widespread acceptance in the life sciences research community. The high throughput and low cost of sequencing has encouraged researchers to undertake ambitious genomic projects, especially in de novo genome sequencing. Currently, NGS systems generate sequence data as short reads and de novo genome assembly using these short reads is computationally very intensive. Due to lower cost of sequencing and higher throughput, NGS systems now pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 39 publications
2
79
0
Order By: Relevance
“…The reads mapping fold coverage was calculated using qualimap_v2.040. We aimed to get a fold coverage of at least 50X for each genome, which was shown to be adequate for characterization of genomes41.…”
Section: Methodsmentioning
confidence: 99%
“…The reads mapping fold coverage was calculated using qualimap_v2.040. We aimed to get a fold coverage of at least 50X for each genome, which was shown to be adequate for characterization of genomes41.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is worth mentioning that our in silico analyses are based on genome sequences that are still fragmented in a varying number of contigs (ranging from 1 to 56 contigs), having been assembled from a sequence coverage ranging from 45-to 281-fold. Nevertheless, a 50-fold sequence coverage of prokaryotic genomes, as obtained from next-generation sequencing (NGS) platforms, is predicted to represent more than 99% of the complete genome sequence (42), which implies an adequate reliability of the in silico analyses of ANI. Furthermore, it has been shown that for highly related genomes (i.e., ANI values of Ͼ94%), draft genome sequences that reach at least 50% of genome coverage for both strains result in ANI values that have been recognized as adequate for the calculation of nucleotide identity (28).…”
Section: Resultsmentioning
confidence: 99%
“…For an extensive literature on assemblers consult [54,[69][70][71][72][73]. The list of aligners is updated online [53].…”
Section: Platform-specific Biasesmentioning
confidence: 99%